1992
DOI: 10.1180/claymin.1992.027.4.01
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dry heating on the chemistry, surface area, and oxalate solubility of synthetic 2-line and 6-line ferrihydrites

Abstract: Synthetic 2-line and 6-line ferrihydrites were heated to 400 K, 500 K and 600 K, under dry conditions. Heating to 400 K lowered the ratios of structural OH to Fe2O3 without a phase transformation. The lowest ratios observed at 400 K were 1·23 (2-line) and 0·85 (6-line ferrihydrite) after 1150 h. For 6-line ferrihydrites heated to 400 K, the solubility in oxalate and the BET surface areas decreased with increasing heating time, whereas the unit-cell parameters, the relative peak intensities and the mean coheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
52
0
8

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 29 publications
8
52
0
8
Order By: Relevance
“…For the N 2 gas adsorption/desorption isotherms, the samples were first outgassed at 30, 50, or 80 • C at 10 −9 bar for a period of 18 h. For metastable minerals such as HFO, a low outgassing temperature is generally chosen to avoid recrystallization of the sample during measurement. However, Stanjek and Weidler [25] showed that dry heating of two-line ferrihydrite at moderate temperature (125 • C) did not induce recrystallization after 1150 h. The weight loss upon heating is attributed to loss of surface and structural OH groups, but without net changes in unit cell and XRD coherence lengths. Outgassing at 50 and 80 • C in this study serves to control the quality of data obtained at lower outgassing temperature.…”
Section: Surface Area and Porosity By Gas Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the N 2 gas adsorption/desorption isotherms, the samples were first outgassed at 30, 50, or 80 • C at 10 −9 bar for a period of 18 h. For metastable minerals such as HFO, a low outgassing temperature is generally chosen to avoid recrystallization of the sample during measurement. However, Stanjek and Weidler [25] showed that dry heating of two-line ferrihydrite at moderate temperature (125 • C) did not induce recrystallization after 1150 h. The weight loss upon heating is attributed to loss of surface and structural OH groups, but without net changes in unit cell and XRD coherence lengths. Outgassing at 50 and 80 • C in this study serves to control the quality of data obtained at lower outgassing temperature.…”
Section: Surface Area and Porosity By Gas Adsorptionmentioning
confidence: 99%
“…This shows that higher outgassing temperatures provoke a small shift of the pore size distribution toward slightly larger pores, resulting in an increase of the amount of mesopores at the expense of some micropores, and a decrease in specific surface area. These changes are related to the removal of surface hydroxyl groups and possibly some entrainment of structural hydroxyls [25]. Because the extent of Table 1 Total specific surface area, total volume of gas adsorbed (V m ), and C constants obtained by the BET equation fit for N 2 In the case of water, results are shown for two possible adsorption surface areas of the water molecule.…”
Section: Surface Area and Porositymentioning
confidence: 99%
“…This can be used to determine whether IP 6 is associated with mineral or organic material, but cannot indicate whether IP 6 is associated with amorphous or crystalline metal hydroxides. However, extraction in acidic ammonium oxalate is routinely used to extract amorphous Al and Fe hydroxides, as well as associated P (Gleyzes et al, 2002 ) that polarizes and weakens the metal-O bonds between metal atoms and the surface of the metal complex, leading to non-reductive dissolution (Gleyzes et al, 2002;Stanjek and Weidler, 1992;Zinder et al, 1986). Thus, the specificity for amorphous metal complexes is due to their relatively high specific surface area (concentration of OH − per area) leading to a high solubility compared to crystalline forms such as goethite (Karim, 1984;Schwertmann, 1973;Theng et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, even at temperatures much lower than 200°C, some changes in the composition and surface chemistry of the oxyhydroxide may occur. Prolonged heating at [100°C causes ferrihydrite (6L) dehydration and reduction of the specific surface area [59,83]. Under favorable conditions, an intermediate phase between ferrihydrite and hematite may form [84].…”
Section: Xrd and Ftir Analysesmentioning
confidence: 99%
“…The exotherm related to this process is usually noted at temperatures exceeding 300°C [1] or, in case of the natural samples usually containing silicate admixtures, even at higher temperatures [10,[80][81][82]. Dry heating of ferrihydrite at 227°C resulted in evident changes of the XRD patterns recorded after 9 h of the process when approximately one quarter of the oxyhydroxide was converted to hematite [1,83]. On the other hand, even at temperatures much lower than 200°C, some changes in the composition and surface chemistry of the oxyhydroxide may occur.…”
Section: Xrd and Ftir Analysesmentioning
confidence: 99%